Correlation Between Transabdominal Sonographically Measured Prostate Volume with Anthropometric Factor in Normal Healthy Subjects (BIRDEM Medical Journal, 2012)
To investigate the relationship between total prostate volume with anthropometric factor like age, height, weight and BMI. This can be useful in assessing the normality of prostate gland.Method: In 42 normal healthy subjects the length, anteroposterior and transverse diameters of prostate gland were measured & prostate volumes were calculated by using prolate ellipse formula. Age, height, weight of the subjects were recorded and body mass index calculated accordingly.Result: Correlation co-efficient or r test was used to find out the relationship between the variables. P value